2004
DOI: 10.1158/1078-0432.ccr-03-1156
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Consequences of Interleukin 12 Administration after Autologous Stem Cell Transplantation

Abstract: Purpose:The purpose is to determine the immunological effects of recombinant human interleukin (rhIL)-12 therapy after autologous stem cell transplantation.Experimental Design: Twelve patients (8 non-Hodgkin's lymphoma, 2 Hodgkin's disease, and 2 plasma cell myeloma) were treated with rhIL-12 by bolus i.v. injection in doses of 30, 100, or 250 ng/kg starting at a median of 66 days posttransplant. Immunological assays were performed using serum and peripheral blood mononuclear cell (PBMC) samples obtained on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The therapeutic effects of IL-12 have been extensively demonstrated in a variety of animal tumor models when it is administrated either systemically or locally at the tumor site (47). Moreover, the pleiotropic antitumoral characteristics of IL-12 have encouraged the initiation of several clinical trials in patients with different types of cancer like T cell lymphoma (6), non-Hodgkin lymphoma (8, 9), melanoma (10), ovarian cancer (11), Kaposi's sarcoma (12), renal carcinoma (13), and so on.…”
mentioning
confidence: 99%
“…The therapeutic effects of IL-12 have been extensively demonstrated in a variety of animal tumor models when it is administrated either systemically or locally at the tumor site (47). Moreover, the pleiotropic antitumoral characteristics of IL-12 have encouraged the initiation of several clinical trials in patients with different types of cancer like T cell lymphoma (6), non-Hodgkin lymphoma (8, 9), melanoma (10), ovarian cancer (11), Kaposi's sarcoma (12), renal carcinoma (13), and so on.…”
mentioning
confidence: 99%
“…Studies have shown that IL-12 given in conjunction with rituximab for low-grade non-Hodgkin lymphoma is well tolerated and may be associated with longer response duration than previous trials using rituximab alone [11,12]. IL-12 has also been studied after autologous stem cell transplant for hematological malignancies resulting in the expansion of T, B, and NK cells in vivo [13]. Interleukin-12 alone or with GM-CSF has been used to enhance anti-idiotype vaccines in patients with multiple myeloma [14].…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Recent reports of combination Gene-modified BMC therapy H Wang and TC Thompson therapy with immune cytokines and BM transplantation appear to provide specific advantages and a new direction for cancer therapy. 54,55 Mesenchymal stem cell vehicles. The adherent fraction of BMCs contains differentiated mesenchymal BM stromal cells and pluripotent mesenchymal stem cells (MSCs) that give rise to differentiated cells that belong to the osteogenic, chondrogenic, adipogenic, myogenic and fibroblastic lineages.…”
Section: Differentiated Immune Cell Vehiclesmentioning
confidence: 99%